Nontargeted metabolomics: PTFI Platform - Watkins, Steve; Odenkirk, Melanie T; Prenni, Jessica; Brinkley, Sarah (2025)
The PTFI Nontargeted Metabolomics platform supports the characterization of the small molecule composition in food. This method uses solid phase extraction (SPE) to isolate small molecules for analysis by reverse phased liquid chromatography-high resolution mass spectrometry (LC-HRMS).